STEP Schools Agri-Competition (Maiden edition) - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2022)
The Innovative Youth in Agriculture (I-Youth Project) presents the maiden edition of STEP Schools Agri-Competition. Changing the perception and improving academic performance of students in agriculture.